HERBAL THERAPY SUPPRESS INTERLEUKIN-1β IN PERIODONTITIS AND TYPE 2 DIABETES MELLITUS - Padang, Lastry Ruth; Syaify, Ahmad; Karina, Vincensia Maria (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2025)
Background: Interrelated pathological conditions such as periodontitis and Type 2 Diabetes Mellitus (T2DM) still be the mistery to solve. The production of secondary metabolites due to hyperglycemia conditions, namely AGEs, contributes to inflammation that arises in periodontal tissue. Periodontal inflammation is exacerbated by systemic dysregulation resulting in periodontitis being one of the potential complications aggravating the condition of T2DM. Excessive production of pro-inflammatory cytokines damages periodontal tissue and pancreas B cells and thus leads to insulin resistance. Many approach have been conducted to break the relationship between these two diseases, especially from the inflammatory pathway. Herbal therapy is one of the potential treatment to manage the bidirectional relationship.  Objective: The aim of this study is to elaborate the effects of herbal therapy on decreasing IL-1β cytokines as potential targeted therapeutic targets for both periodontitis and type 2 diabetes condition.Methods: Literature research done from 2013 to 2023 to find relevant articles. Result: Several herbal therapies effective in decreased Interleukin-1β and correlated to systemic and periodontal condition. Conclusion:Herbal therapy is effectively decreasing Interleukin-1β as a potential therapeutic target in periodontitis and Diabetes Mellitus Type 2 management.